Overtraining of aerobic physical exercise reduce rats (Rattus norvegicus) memory - Ni Made Ridla Parwata (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2020)
Overtraining syndrome is a decrease in physical capacity, emotions and immunity due to training that is too often without adequate periods of rest. Overtraining is often experienced by athletes who daily undergo heavy training with short break periods. This research aims to look at the effect of overtraining aerobic physical exercise on memory in mice. The research method was experimental in vivo with the subject of adult male rat (Rattus Norvegicus) Winstar strain aged 8-10 weeks, body weight 200-250 gr. Divided into three groups, namely the control group, aerobic group and overtraining group. The results of memory tests with water E Maze showed an increase in the duration of travel time and the number of animal errors made by the overtraining group (p = 0.003). This study concludes that overtraining aerobic physical exercise can reduce memory in rat hippocampus.